Coordination determinants of technical skills of young female tennis players - Waldzinska, E.; Waldzinski, T.; Niznikowski, T. (Theory and Practice of Physical Culture, 2021)
Objective of this study was to obtain knowledge on coordination determinants of technical skills of female tennis players aged 9 and 11.